The relationship between university social responsibility, digital transformation and intention to continue using E-learning in private university - Le, Quoc Thang; Le, Thanh Tiep (Journal of Finance - Marketing Research, 2025)
This study examines the relationship between university social responsibility (USR), digital transformation (DGT) and online learning continuation intention (ELE) in private universities. Furthermore, this relationship is also studied in the context of the role of student satisfaction (SSA). In addition, the study also assesses the impact of several factors on USR, such as education (EDU), awareness (COG), society (SOC), and organization (ORG). There are several factors that influence digital transformation such as lecturers (LEC), students (STU), and universities (UNI). The study used both qualitative and quantitative methods. The survey collected 459 responses which were used to analyze the data in a partial-least square structural equation model (PLS-SEM). The analysis results showed that USR and DGT had a positive impact on the intention to continue choosing online training, especially taking into account the influence of SSA in that correlation. In addition, the results also provided further evidence for the simultaneous impact of the above factors. This is a new point compared to previous individual studies, in addition to the evidence that reinforces the application of research theoretical foundations. At the same time, the study suggests the managerial implications related to infrastructure investment for digital transformation and policy mechanisms to attract good lecturers. Besides, this study has provided supplementary policy mechanisms to support learners and pay attention to social responsibility in building development strategies for private universities.